TOTAL BENCHMARKING : RASIO DAN PEMANFAATANNYA - Verawati Suryaputra (Center for Economic Studies Universitas Katolik Parahyangan, 2012)
Total Benchmarking is a standard issued by Directorate General of Taxation which is used to appraise Taxpayers on the fairness of Financial Report and the obedience to comply with Tax Laws. The Benchmark consists of 14 Ratios that differ among industries. Until now, The Directorate General of Taxation has published Total Benchmark for 100 industries. If there are differences between taxpayer’s ratio and the benchmark, do not mean that the taxpayer didn’t fulfill his obligation according to the Tax Laws. The analyst (Account Representative) should use this benchmark as a tool to plan for further analysis. The data used to construct this benchmark taken from samples in each industry for the period of 2005, 2006, and 2007 which is differ from current condition. Therefore the writer suggest adjustment for this benchmark.Key words : Total Benchmarking